The effectiveness of open-ended versus closed-ended questioning on student participation in middle school EFL classes: conceptual foundations and methodology - Turgunova, Laziza Anvarovna; Shamsutdinova, Lyutsiya Rafailovna (The Lingua Spectrum, 2026)
This article explores the conceptual foundations and methodological approaches to investigating the effectiveness of open-ended and closed-ended questioning techniques on student participation in middle school English as a Foreign Language (EFL) classrooms. The paper analyzes the theoretical origins of teacher questioning research and highlights the importance of questioning strategies in linguistic research and foreign language teaching methodology. Emphasis is placed on the role of cognitive demand, classroom interaction patterns, and authentic communicative context in shaping student participation behavior. The article reviews research methods applicable to the study of questioning effectiveness and suggests directions for further investigation. Drawing on Long’s Interaction Hypothesis, Swain’s Output Hypothesis, and Bloom’s revised taxonomy, the study demonstrates how open-ended questioning integrated with authentic materials produces substantially greater gains in student participation frequency, response length, speaking proficiency, and affective attitudes compared to traditional closed-ended approaches. The findings also emphasize the importance of learner-centered instruction, critical thinking development, and interactive classroom environments in improving communicative competence and motivating students to actively engage in foreign language learning processes.